Preparation of dipalmitin by fractionation method / Normah Ismail, Cheow Chong Seng and Chong Chiew Let - Ismail, Normah; Cheow, Chong Seng; Chong, Chiew Let (Research Management Institute (RMI), 2011)
Dipalmitin was prepared by glycerolysis of palmitic acid in the presence of isooctane and Lipozyme RM 1M and was further purified by neutralization followed by fractionation. Dipalmitin containing samples was named as 'diacylglycerol chemical method' (DGCHM). The dipalmitin content in DGCHM was 71.83%, however, after fractionation, this percentage was raised to 89.80%. The DGCHM and RBDPO (refined bleached and deodorized palm oil) added with DGCHM were analysed for their crystallization behavior. The complete melting temperature for DGCHM was 70.7°C. The combined DSC and wide-angle XRD of the dipalmitin revealed the polymorphic transformation from α to sub α to α. The yield for DGCHM was 71% (w/w). The purification of dipalmitin by fractionation method was considerably practical due to the higher yield, easier preparation, shorter preparation time and smaller amounts of starting materials required. The addition of 1% DGCHM to RBDPO has a negligible effect on its crystallization and heating properties.